Mission to Paris [large type] a novel - Furst, Alan (Thorndike Press large print core, 2012)
Arriving in Paris on the eve of the Munich Appeasement in 1938, Hollywood star Frederic Stahl is unwittingly entangled in the region's shifting political currents when he discovers that his latest film is linked to the destinies of fascists, German Nazis, and Hollywood publicists.